2004
DOI: 10.1093/brain/awh012
|View full text |Cite
|
Sign up to set email alerts
|

Does cerebrovascular disease affect the coupling between neuronal activity and local haemodynamics?

Abstract: The relationship between neurophysiological and cerebrovascular-metabolic findings in patients affected by severe cerebrovascular deficits was investigated by comparing magnetoencephalographic (MEG-evoked fields) and blood oxygen level-dependent functional MRI (BOLD fMRI) responses to median nerve electric stimulation. Despite the use of identical stimuli, the two techniques elicited always-detectable responses in the control group (10 subjects), but demonstrated uncorrelated activation properties in our patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
156
3
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(173 citation statements)
references
References 50 publications
12
156
3
2
Order By: Relevance
“…Kim et al (2005) discussed stroke-related alterations in hemodynamic coupling, which were controversially reported in human BOLD fMRI studies of sensorimotor stroke recovery (Pineiro et al, 2002;Rossini et al, 2004;Krainik et al, 2005). Two of these human studies reported a decreased BOLD signal in both affected and unaffected sensorimotor cortices of stroke patients compared with age-matched controls (Pineiro et al, 2002;Rossini et al, 2004). In contrast to these observations, we did not observe uncoupling of neuronal activity and BOLD response in both hemispheres but a coupled alteration of both neuronal activity and hemodynamic response.…”
Section: Preservation Of Neurovascular Coupling After Strokecontrasting
confidence: 61%
See 2 more Smart Citations
“…Kim et al (2005) discussed stroke-related alterations in hemodynamic coupling, which were controversially reported in human BOLD fMRI studies of sensorimotor stroke recovery (Pineiro et al, 2002;Rossini et al, 2004;Krainik et al, 2005). Two of these human studies reported a decreased BOLD signal in both affected and unaffected sensorimotor cortices of stroke patients compared with age-matched controls (Pineiro et al, 2002;Rossini et al, 2004). In contrast to these observations, we did not observe uncoupling of neuronal activity and BOLD response in both hemispheres but a coupled alteration of both neuronal activity and hemodynamic response.…”
Section: Preservation Of Neurovascular Coupling After Strokecontrasting
confidence: 61%
“…Here, we show that, during the first 7 weeks after 1 h of MCA occlusion, the neurovascular coupling remains preserved at all times. Kim et al (2005) discussed stroke-related alterations in hemodynamic coupling, which were controversially reported in human BOLD fMRI studies of sensorimotor stroke recovery (Pineiro et al, 2002;Rossini et al, 2004;Krainik et al, 2005). Two of these human studies reported a decreased BOLD signal in both affected and unaffected sensorimotor cortices of stroke patients compared with age-matched controls (Pineiro et al, 2002;Rossini et al, 2004).…”
Section: Preservation Of Neurovascular Coupling After Strokementioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of these changes in hemodynamics, neuronal activity is not necessarily coupled to regional CBF and CBV changes to the same degree as in healthy subjects. Rossini et al (2004) performed a combined Figure 2 Representative block-averaged time courses for (A) a control subject and (B-D) three patients. Gray areas depict the stimulus period.…”
Section: Hemometabolic Uncouplingmentioning
confidence: 99%
“…BOLD-dependent capillary density and draining veins and the perfusion of brain tissue may differ between damaged and undamaged tissues, especially at acute stages of stroke. fMRI activation can even be lost in stroke patients because of altered vasomotor reactivity, demonstrating uncoupling of neuronal activity and fMRI activation (Rossini et al, 2004;Binkofski & Seitz 2004;Murata et al, 2006). In our study, paretic hand movement at the acute stage resulted in reduced motor cortex activation in the damaged hemisphere, especially in patients with cortical infarction.…”
Section: Wwwintechopencommentioning
confidence: 46%